Risk Behaviors among Undocumented Immigrants in Northern Mexico: 2006-2007 - Marcela Agudelo Botero; Martha Cecilia Jaramillo Cardona (Social Medicine Publication Group, 2011)
Introduction: The purpose of this study was to analyze some major aspects of health of the undocumented migrant population at the northern Mexican border (Tijuana and Mexicali) between 2006 and 2007. Methods: We used a database of 1,535 interviews with undocumented migrants conducted by Doctors of the World. This sample is not random, and therefore not necessarily representative of all migrants in circumstances similar to those of the individuals covered in this study. Results: Among the migrants, alcohol consumption had diminished during their travels, while smoking and drug-taking increased. Migrants also frequently engaged in unprotected sex and exchanged sex for other privileges. We found that a significant proportion of the migrants suffered physical and psychological violence perpetrated mainly by police authorities. Conclusions: The issues faced by migrants should be included in political and academic agendas in order to better understand the challenges faced by this population and to provide insight into their true situation, with a view to proposing targeted public policies.